Đặc điểm nhân cách của người giảng viên giảng dạy nghệ thuật thực hành múa - Lê, Quỳnh Trang (Tạp chí Thiết bị Giáo dục, 2023)
Along with the development of society, dance has constantly changed to fulfill its role and function well. The competition to keep the lines of national art, ethnic dance, dance also changes to enrich to create new identities of this art. The development of the society along with the requirements of spiritual values that the dance of singing to people asked the instructors of the dance of performing arts have special characteristics of the personality changed with its to the past.